Development of PPAR-agonist GW0742 as antidiabetic drug: study in animals - Niu HS; Ku PM; Niu CS; Cheng JT; Lee KS (Dove Medical Press, 2015)
Ho-Shan Niu,1 Po-Ming Ku,2,3 Chiang-Shan Niu,1 Juei-Tang Cheng,3,4 Kung-Shing Lee5–71Department of Nursing, Tzu Chi College of Technology, Hualien City, 2Department of Cardiology, 3Department of Medical Research, Chi-Mei Medical Center, Yong Kang, Tainan City, 4Institute of Medical Sciences, Chang Jung Christian University, Guiren, Tainan City, 5Department of Surgery, Division of Neurosurgery, Pingtung Hospital, 6Department of Surgery, Kaohsiung Medical University, 7School of Medicine, Chung-Ho Memorial Hospital, Kaohsiung Medical University, Kaohsiung City, TaiwanBackground: The development of new drugs for the treatment of diabetes mellitus (DM) is critically important. Insulin resistance (IR) is one of the main problems associated with type-2 DM (T2DM) seen in clinics. GW0742, a selective peroxisome proliferator-activated receptor (PPAR)-δ agonist, has been shown to ameliorate metabolic abnormalities including IR in skeletal muscle in mice fed high-fructose corn syrup. However, the influence of GW0742 on systemic insulin sensitivity has still not been elucidated. Therefore, it is important to investigate the effect of GW0742 on systemic IR in diabetic rats for the development of new drugs.Methods: The present study used a T2DM animal model to compare the effect of GW0742 on IR using homeostasis model assessment-IR (HOMA-IR) and hyperinsulinemic euglycemic clamping. Additionally, the insulinotropic action of GW0742 was investigated in type-1 DM (T1DM) rats. Changes in the protein expression of glucose transporter 4 (GLUT4) and phosphoenolpyruvate carboxykinase (PEPCK) in skeletal muscle and in liver, respectively, were also identified by Western blots.Results: GW0742 attenuated the increased HOMA-IR in diabetic rats fed a fructose-rich diet. This action was blocked by GSK0660 at the dose sufficient to inhibit PPAR-δ. Improvement of IR by GW0742 was also characterized in diabetic rats using hyperinsulinemic euglycemic clamping. Additionally, an increase of insulin sensitivity due to GW0742 was observed in these diabetic rats. Moreover, GW0742 reduced the hyperglycemia in T1DM rats lacking insulin. Western blotting analysis indicated that GW0742 reversed the decrease in GLUT4 and markedly reduced the increased PEPCK in liver.Conclusion: The data showed that GW0742 has the ability to improve glucose homeostasis in diabetic rats through activation of PPAR-δ. Therefore, PPAR-δ is a good target for the development of antidiabetic drugs in the future.Keywords: insulin resistance, fructose-rich chow, HOMA-IR, streptozotocin, insulinotropic action, rats